LONG-TERM EFFECT OF CONTINUOUS POSITIVE AIRWAY PRESSURE THERAPY (CPAP) IN HYPERTENSIVE PATIENTS WITH SLEEP APNEA AND METABOLIC IMPAIRMENT - M. V. Gorbunova; S. L. Babak; A. G. Maliavin (SINAPS LLC, 2017)
Objective: Obstructive sleep apnea (OSA) is associated with the high prevalence of cardiovascular diseases, and such disease manifestations as obesity, arterial hypertension (AH), violation of carbohydrate metabolism, dyslipidemia and endothelial dysfunction. However, the effects of Continuous Positive Airway Pressure therapy (Continuous Positive Airway Pressure - CPAP therapy) on the normalization of blood pressure in patients with OAS+AH are poorly understood and poorly studied. The aim of the study was to investigate 12-month effects of long-term CPAP-therapy with auto-adaptation to inhalation and exhalation (A-Flex therapy) on blood pressure in patients with OSA+AH. Methods: To the prospective single-center study were included 177 patients with snoring, metabolic disorders, obstructive sleep apnea, and hypertension with the established drug therapy (138 men [78%] and 37 females [21%]), in age interval of 35-75 years (56,4 ± 9,4) which apnea-hypopnea index (AHI) > 5 event/hour. The night polygraphy study (PG) was performed to calculate AHI, oxygen desaturation index (ODI), mean nocturnal saturation (Sp02 mean) by the rules of American Academy of Sleep Medicine (AASM). Optimal level of A-Flex therapy was adjusted at home. AHI, the level of air leakage, average pressure and compliance to CPAP treatment were established in accordance with international requirements. Results: After 12 months of A-Flex therapy we found a significant decrease of level of systolic and diastolic blood pressure. The group of CPAP-therapy has decreased daytime SBP on -5.9 mmHg (95% Cl from -3.2 to -7.1; P=0.02) and night SBP on -4.1 mmHg (95% Cl from -6.1 to -2.6; P=0.01). Similar dynamics was observed in variations of DBP. The group of CPAP-therapy decreased daytime DBP on -1.1 mm Hg (95% Cl from -2.2 to -0.5; P=0.02) and nighttime DBP on -5.1 mm Hg (95% Cl from -7.2 to -3.5; P=0.01). In addition, the group of CPAP-therapy have clinical changing of excessive daytime sleepiness, expanding physical activity, normalization of night sleep. Conclusions: The 12-month A-Flex therapy in OSA patients with AH has a significant therapeutic effect of stabilization systolic and diastolic blood pressure. The long-term 12-month A-Flex therapy has to reduce the risks of cardiovascular events in moderate and severe OSA patients with acute metabolic manifestations and arterial hypertension.